Life satisfaction and aggressive behavior of football fans - Kostencka, Alicja; Wronkowski, Maciej (Contemporary problems of physical and health culture, 2022)
The aim of this article is to show – on the basis of the results of my own research – the relationship between the level of life satisfaction (LS) and the declared, aggressive behavior of members of the scarf subculture (i.e. participation in spontaneous fights of fans before/ after or during the match), taking into account their belonging to specific fan groups. The study used the method of a diagnostic survey with the questionnaire technique. The questionnaire used in the study was prepared in an electronic form, which was posted on the Facebook social network in websites associating football fans. Two statistical methods were also used in this study: chisquare test (Pearson test) and analysis of variance (Anova). The results of the research indicate that involvement in the fan movement may lead to the feeling of high satisfaction with life. In the presented study, fans involved in the fan movement experienced high satisfaction with life - despite aggressive or very aggressive behavior – as well as people who did not show aggressive behavior.